Urgensi Penyatuan Lembaga Penegak Hukum di Laut Indonesia - Ridha, Andi Muhammad; Heri, Mohammad; Setiaji, Bayu Tri (Universitas Batanghari Jambi, 2024)
In its efforts to enforce law at sea, Indonesia has 13 law enforcement agencies at sea. Six of these institutions have maritime patrol task forces. The number of law enforcement agencies in Indonesian seas is considered negative by several parties because of the potential for the authority of each agency to overlap. This research aims to find out what the condition of maritime law enforcement agencies in Indonesia is and what are the considerations for unifying maritime law enforcement agencies in Indonesia. This research is normative research related to maritime law enforcement agencies in Indonesia. There are at least 13 law enforcement agencies in Indonesian seas. The unification of maritime law enforcement agencies in Indonesia is necessary because unclear roles and authority, as well as a lack of coordination between agencies, have resulted in ineffectiveness in law enforcement and maritime security management. Indonesia needs unification of authority to strengthen all security, safety and maritime law enforcement functions in Indonesia